Perovskite type fuel electrode, preparation method thereof and reversible solid oxide battery
By forming a heterostructure of "metal nanoparticles-perovskite oxide" in the perovskite fuel electrode and modifying the metal oxide nanoparticles on the outer surface, the problems of insufficient electrocatalytic activity and stability of the perovskite fuel electrode in the SOFC and SOEC modes are solved, and excellent electrocatalytic activity in the dual mode is achieved.
Patent Information
- Application Number
- CN202411646320.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing perovskite fuel electrodes have insufficient electrocatalytic activity in SOFC and SOEC modes, especially in SOEC mode, and have poor stability.
ABO3 perovskite oxides with A-position defects and B-position doped metals were treated in a reducing atmosphere by in-situ precipitation method to form a heterostructure of "metal nanoparticles-perovskite oxides", and metal oxide nanoparticles were modified on the outer surface by hydrothermal method to improve electrocatalytic activity and stability.
The electrocatalytic activity of perovskite fuel electrodes in SOFC and SOEC modes is significantly enhanced, and the electrocatalytic activity of perovskite fuel electrodes is maintained, while improving the stability of the electrodes.
Smart Images

Figure CN119601685A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field related to batteries, and in particular relates to a perovskite fuel electrode and a preparation method thereof, and a reversible solid oxide battery. Background Art
[0002] Reversible Solid Oxide Cell (RSOC) is a highly efficient energy conversion device that can operate in a fuel cell (SOFC) mode to directly convert the chemical energy of fossil fuels such as natural gas and secondary energy such as hydrogen into electrical energy, effectively improving the utilization rate of fuels; it can also operate in an electrolysis cell (SOEC) mode to use intermittent renewable clean energy such as solar energy, wind energy, tidal energy and "valley electricity" to electrolyze carbon dioxide, electrolyze water, and co-electrolyze carbon dioxide and water to generate carbon monoxide, hydrogen, synthesis gas, etc., thereby storing excess energy in the form of chemical energy.
[0003] Reversible solid oxide cells are mainly composed of fuel electrodes, electrolytes and air electrodes. Fuel conversion in SOFC mode and carbon dioxide reduction and water decomposition in SOEC mode are all carried out on the fuel electrode. Currently, the most mature Ni-based metal ceramic fuel electrode has poor resistance to carbon deposition and sulfur resistance in hydrocarbon fuel atmospheres, and Ni particles are prone to agglomeration after long-term operation, affecting the electrocatalytic activity and stability. ABO3 perovskite-type electrode materials are considered to be RSOC fuel electrode materials that are expected to replace Ni-based metal ceramics due to their good chemical and mechanical stability and high mixed ion-electron conductivity. However, the catalytic activity of perovskite-type fuel electrodes is not yet comparable to that of Ni-based metal ceramic fuel electrodes, and needs to be further improved.
[0004] To address this problem, researchers have proposed methods such as vapor deposition, solution impregnation, and in-situ precipitation to improve the electrocatalytic activity of perovskite fuel electrodes. Among them: the vapor deposition method has a slow deposition rate and high operating costs; the solution impregnation method is simple to operate, but the impregnated nanoparticles tend to agglomerate after long-term operation at high temperatures, thereby reducing the catalytic performance; the perovskite fuel electrode improved by the in-situ precipitation method has good electrocatalytic activity only in the SOFC mode during reversible operation, but the enhancement effect on the electrocatalytic activity in the SOEC mode is relatively limited. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a perovskite fuel electrode and a preparation method thereof, and a reversible solid oxide battery, wherein the perovskite fuel electrode exhibits excellent electrocatalytic activity in both SOFC mode and SOEC mode.
[0006] The inventive concept of the present invention is: on the one hand, the ABO3 type perovskite oxide with A-site defects and B-site doped metal is treated with a reducing atmosphere by an in-situ precipitation method, so that the doped metal is precipitated in situ in the form of nanoparticles embedded in the matrix, forming a "metal nanoparticle-perovskite oxide" heterostructure with strong binding force, which not only improves the catalytic activity of the fuel electrode, but also enhances the stability of the fuel electrode, so that the fuel electrode can significantly enhance the electrocatalytic activity in the SOFC mode during the reversible operation. On the other hand, without affecting the in-situ precipitation of metal elements of the perovskite fuel electrode, the metal oxide nanoparticles are modified on the outer surface of the "metal nanoparticle-perovskite oxide" heterostructure by hydrothermal treatment to regulate the physicochemical properties of the hydrothermally modified fuel electrode, thereby enhancing the electrocatalytic activity in the SOEC mode, while maintaining a good electrocatalytic activity in the SOFC mode. Therefore, the perovskite fuel electrode prepared by the present invention is applied to a reversible solid oxide battery, and exhibits excellent electrocatalytic activity in both the SOFC mode and the SOEC mode.
[0007] In order to solve the above technical problems, the first aspect of the present invention provides a perovskite fuel electrode, comprising metal nanoparticles, perovskite oxide and metal oxide nanoparticles; the metal nanoparticles are in situ precipitated on the surface of the perovskite oxide and form a heterostructure with the perovskite oxide; the metal oxide nanoparticles are modified on the outer surface of the perovskite oxide.
[0008] In some embodiments of the present invention, the metal nanoparticles are transition metals, such as at least one of nickel, iron, cobalt, and ruthenium.
[0009] In some embodiments of the present invention, the particle size of the metal nanoparticles is 30-120 nm.
[0010] Specifically, the particle size of metal nanoparticles is related to the size of perovskite oxide and the reduction treatment conditions. For example, the size of perovskite oxide synthesized by solvent method is about several hundred nanometers, and the particle size of metal nanoparticles precipitated in situ is about 30-60nm; the size of perovskite oxide synthesized by solid phase method is about several microns, and the particle size of metal nanoparticles precipitated in situ is about 60-120nm. However, metal nanoparticles with a particle size of 30-120nm have a good enhancement effect on the electrocatalytic activity of fuel electrodes.
[0011] In some embodiments of the present invention, the metal oxide nanoparticles include at least one of cerium oxide, nickel oxide, iron oxide, copper oxide, and zinc oxide. Studies have shown that these oxides are beneficial to improving the electrocatalytic activity of fuel electrodes.
[0012] In some embodiments of the present invention, the particle size of the metal oxide nanoparticles is less than 10 nm.
[0013] Specifically, nano-sized metal oxide particles are more conducive to improving the activity of the fuel electrode and reducing the loading of the target metal oxide particles. The study found that regardless of whether the size of the perovskite oxide is a few hundred nanometers or a few micrometers, and regardless of whether the particle size of the in-situ precipitated metal nanoparticles is 30-60nm or 60-120nm, the particle size of the hydrothermally modified metal oxide nanoparticles is less than 10nm, indicating that the properties of the hydrothermally modified metal oxide nanoparticles on the fuel electrode surface are not affected by the modified body.
[0014] In some embodiments of the present invention, the molar ratio of the metal nanoparticles to the perovskite oxide is (0.04-0.08):1.
[0015] In some embodiments of the present invention, the mass ratio of the metal oxide nanoparticles to the perovskite oxide is (0.5-2.5):100.
[0016] A second aspect of the present invention provides a method for preparing a perovskite-type fuel electrode, the method being used to prepare the above-mentioned fuel electrode material, comprising the following steps:
[0017] (1) synthesizing ABO3 type perovskite oxide with A-site defect and B-site metal doping to obtain electrode powder;
[0018] (2) adding the electrode powder to a metal nitrate aqueous solution to carry out a hydrothermal reaction, and after centrifugation, washing with water, and drying, calcining in an air atmosphere to obtain an electrode powder modified with metal oxide nanoparticles;
[0019] (3) The electrode powder modified with the metal oxide nanoparticles is subjected to heat treatment in a reducing atmosphere to precipitate metal nanoparticles in situ on the surface of the electrode powder, thereby obtaining the perovskite fuel electrode.
[0020] In some embodiments of the present invention, in step (1), the synthesis method of the ABO3 type perovskite oxide includes a solid phase method, a sol-gel method or a solvothermal method. Wherein: A represents an alkaline earth metal or rare earth metal ion, and the A-site defect is required not to change the crystal phase structure of the perovskite; B represents a transition metal ion, such as at least one of nickel, iron, cobalt, and ruthenium. For example, the fuel electrode material La 0.43 Ca 0.37 Ti0.94 Ni 0.06 O 3-δ (LCTN) is an ABO3 type perovskite fuel electrode material, and the molar ratio of transition metal Ni doped at the B site to perovskite oxide is 0.06:1.
[0021] In some embodiments of the present invention, in step (2), the metal nitrate aqueous solution is selected from at least one of cerium nitrate, nickel nitrate, iron nitrate, copper nitrate and zinc nitrate. By controlling the concentration of the metal nitrate aqueous solution and extending or shortening the hydrothermal reaction time, the content of the hydrothermally modified metal oxide on the outer surface of the electrode powder can be controlled.
[0022] In some embodiments of the present invention, in step (2), the concentration of the metal nitrate aqueous solution is 0.05-0.5 mol / L.
[0023] In some embodiments of the present invention, in step (2), the molar ratio of the electrode powder to the metal nitrate is (0.5-8.5):1.
[0024] In some embodiments of the present invention, in step (2), the temperature of the hydrothermal reaction is 120-180°C.
[0025] In some embodiments of the present invention, in step (2), the hydrothermal reaction time is 1-10 hours.
[0026] In some embodiments of the present invention, in step (2), the calcination temperature is 600-800° C. The purpose of calcination is mainly to decompose the surface-modified nitrate to obtain metal oxide nanoparticles.
[0027] In some embodiments of the present invention, in step (2), the calcination time is 2-4 hours.
[0028] In some embodiments of the present invention, in step (3), the temperature of the heat treatment is 750-800° C. The purpose of heat treatment under a reducing atmosphere is mainly to precipitate the doped metal elements in the perovskite oxide in situ to obtain metal nanoparticles. The in-situ precipitated metal nanoparticles form a heterostructure with the perovskite oxide matrix; the surface-modified metal oxide nanoparticles are uniformly attached to the outer surface of the "metal nanoparticle-perovskite oxide" heterostructure.
[0029] In some embodiments of the present invention, in step (3), the heat treatment time is 1-3 hours.
[0030] In some embodiments of the present invention, in step (3), the reducing atmosphere is any one of hydrogen, a hydrogen / nitrogen mixture, a hydrogen / helium mixture, and a hydrogen / argon mixture.
[0031] A third aspect of the present invention provides a reversible solid oxide battery, the raw materials for preparing the battery include the above-mentioned perovskite fuel electrode, or include the perovskite fuel electrode prepared by the above-mentioned preparation method.
[0032] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0033] The perovskite fuel electrode of the present invention comprises metal nanoparticles, perovskite oxide and metal oxide nanoparticles, wherein: the metal nanoparticles are in-situ precipitated on the surface of the perovskite oxide, and form a "metal nanoparticle-perovskite oxide" heterostructure with strong binding force with the perovskite oxide, which not only improves the catalytic activity of the fuel electrode, but also enhances the stability of the fuel electrode, so that the fuel electrode significantly enhances the electrocatalytic activity in the SOFC mode during the reversible operation; at the same time, the outer surface of the "metal nanoparticle-perovskite oxide" heterostructure is modified with metal oxide nanoparticles by a hydrothermal method, which can not only maintain a good electrocatalytic activity in the SOFC mode, but also significantly enhance the electrocatalytic activity in the SOEC mode. Therefore, the perovskite fuel electrode prepared by the present invention exhibits excellent electrocatalytic activity in both SOFC and SOEC dual modes, and can be applied to reversible solid oxide batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 X-ray powder diffraction pattern of the perovskite fuel electrode prepared in Example 1-3 of the present invention;
[0035] Figure 2 The scanning electron microscope image and EDS spectrum image of the perovskite fuel electrode prepared in Examples 1-3 of the present invention;
[0036] Figure 3 X-ray powder diffraction patterns of the perovskite fuel electrodes prepared in Examples 4-6 and Comparative Example 1 of the present invention;
[0037] Figure 4 This is a scanning electron microscope image of the perovskite fuel electrode prepared in Example 4 of the present invention;
[0038] Figure 5 The electrochemical impedance spectra of the solid oxide single cells prepared in Examples 1-3 of the present invention;
[0039] Figure 6 This is a RSOC performance diagram of the solid oxide single cell prepared in Example 1 of the present invention;
[0040] Figure 7 Electrochemical impedance spectra of solid oxide symmetrical batteries prepared in Examples 4-6 and Comparative Example 1 of the present invention;
[0041] Figure 8 The electrochemical impedance spectrum of the solid oxide single cell prepared in Comparative Example 2 of the present invention;
[0042] Fig. 9 The electrochemical impedance spectrum of the solid oxide single cell prepared in Comparative Example 3 of the present invention;
[0043] Fig.10 This is the electrochemical impedance spectrum of the solid oxide single cell prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION
[0044] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0045] Example 1
[0046] A method for preparing a perovskite fuel electrode material comprises the following steps:
[0047] (1) Synthesis of La 0.43 Ca 0.37 Ti 0.94 Ni 0.06 O 3-δ (LCTN) electrode powder
[0048] LCTN was synthesized by solvothermal method: according to La 0.43 Ca 0.37 Ti 0.94 Ni 0.06 O 3-δ Lanthanum nitrate hexahydrate, calcium nitrate tetrahydrate and nickel nitrate hexahydrate are weighed in a stoichiometric ratio, dissolved in an appropriate amount of polyethylene glycol (PEG-400), stirred continuously at 60°C, and the required amount of tetrabutyl titanate is added dropwise. After stirring for about 1 hour, the above solution is transferred to a polytetrafluoroethylene-lined reactor and crystallized at 180°C for 10 hours. After centrifugation, ethanol washing and drying, the solution is sintered at 900°C in air for 5 hours to obtain LCTN electrode powder.
[0049] (2) Preparation of LCTN modified by cerium oxide hydrothermally
[0050] Using the hydrothermal synthesis method, 0.5 g of LCTN electrode powder was added to 50 mL of 0.005 mol·L -1 The LCTN was prepared by crystallizing the LCTN in an aqueous solution of cerium nitrate hexahydrate at 150°C for 2 hours, centrifuging, washing and drying, and then sintering at 800°C in air for 2 hours, thereby obtaining LCTN hydrothermally modified with cerium oxide, which was designated as LCTN-Ce005M-2h.
[0051] (3) Reduction treatment
[0052] The LCTN-Ce005M-2h electrode powder was treated in pure hydrogen at 750°C for 2 hours to obtain a perovskite-type fuel electrode with in-situ precipitation of metallic nickel nanoparticles modified on the surface of cerium oxide.
[0053] A method for preparing a solid oxide single cell comprises the following steps:
[0054] The LCTN-Ce005M-2h hydrothermally modified with cerium oxide prepared in step (2) of this embodiment was mixed with 96% pine alcohol and 4wt% ethyl cellulose in a mass ratio of 1.5:1 to prepare an electrode slurry, which was coated on La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3-δ (LSGM) solid electrolyte side, La coated between the fuel electrode and the electrolyte 0.4 Ce 0.6 O 2-δ (LDC) as an isolation layer. La with a mass ratio of 1:1 is coated on the other side of the LSGM solid electrolyte. 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ (LSCF) and Gd 0.1 Ce 0.9 O 1.95 The mixture of (GDC) was used as the air electrode. Then, it was calcined in air at 1100°C for 5 hours to obtain a solid oxide single cell. The thickness of the fuel electrode and the air electrode was about 20 μm, and the thickness of the isolation layer was about 5 μm.
[0055] Example 2
[0056] The difference between Example 2 and Example 1 is only that step (2) is different, which is as follows:
[0057] Using the hydrothermal synthesis method, 0.5 g of LCTN electrode powder was added to 50 mL of 0.005 mol·L -1The LCTN was prepared by crystallizing the LCTN in an aqueous solution of cerium nitrate hexahydrate at 150 °C for 4 hours, centrifuging, washing and drying, and then sintering at 800 °C in air for 2 hours, thereby obtaining LCTN hydrothermally modified with cerium oxide, which was designated as LCTN-Ce005M-4h.
[0058] Example 3
[0059] The difference between Example 3 and Example 1 is only that step (2) is different, specifically:
[0060] Using the hydrothermal synthesis method, 0.5 g of LCTN electrode powder was added to 50 mL of 0.02 mol·L -1 The LCTN was prepared by crystallizing the cerium oxide in an aqueous solution of cerium nitrate hexahydrate at 150 °C for 4 hours, centrifuging, washing and drying, and then sintering at 800 °C in air for 2 hours, thereby obtaining LCTN hydrothermally modified with cerium oxide, which was designated as LCTN-Ce02M-4h.
[0061] Example 4
[0062] A method for preparing a perovskite fuel electrode material comprises the following steps:
[0063] (1) Synthesis of La 0.43 Ca 0.37 Ti 0.94 Ni 0.06 O 3-δ (LCTN) electrode powder
[0064] LCTN was synthesized by solid phase method: according to La 0.43 Ca 0.37 Ti 0.94 Ni 0.06 O 3-δ Lanthanum oxide, calcium carbonate, titanium dioxide and nickel nitrate hexahydrate are weighed in a stoichiometric ratio, an appropriate amount of anhydrous ethanol is added and fully ground, and after the ethanol is completely volatilized, it is sintered at 1000°C in air for 12 hours to form perovskite crystal nuclei; ethanol is added again and fully mixed, and sintered at 1400°C in air for 14 hours to obtain LCTN electrode powder.
[0065] (2) Preparation of LCTN modified by cerium oxide hydrothermally
[0066] Using the hydrothermal synthesis method, 1.0 g of LCTN electrode powder was added to 50 mL of 0.02 mol·L -1 After crystallization at 150°C for 4 hours in a hexahydrate cerium nitrate aqueous solution, the mixture was centrifuged, washed with water, and dried, and then sintered at 800°C in air for 2 hours to obtain cerium oxide hydrothermally modified LCTN, which was recorded as LCTN-Ce.
[0067] (3) Reduction treatment
[0068] The LCTN-Ce electrode powder was treated in pure hydrogen at 800°C for 2 hours to obtain a perovskite-type fuel electrode with in-situ precipitation of metal nickel nanoparticles modified on the surface of cerium oxide.
[0069] A method for preparing a solid oxide symmetrical battery comprises the following steps:
[0070] The LCTN-Ce hydrothermally modified with the unreduced cerium oxide prepared in step (2) of this embodiment was mixed with 96% pine alcohol and 4wt% ethyl cellulose in a mass ratio of 1.5:1 to prepare an electrode slurry, which was coated on the Zr 0.92 Y 0.16 O 2.08 (YSZ) solid electrolyte on both sides; then calcined at 1100°C in air for 5 hours to produce a solid oxide symmetrical cell. The thickness of the fuel electrode is about 20μm.
[0071] Example 5
[0072] The difference between Example 5 and Example 4 is only that step (2) is different, which is as follows:
[0073] Using the hydrothermal synthesis method, 1.0 g of LCTN electrode powder was added to 50 mL of 0.02 mol·L -1 After crystallization at 150°C for 4 hours in an aqueous solution of zinc nitrate hexahydrate, the obtained LCTN was sintered at 800°C in air for 2 hours after centrifugation, water washing and drying, thus obtaining LCTN hydrothermally modified with zinc oxide, which was recorded as LCTN-Zn.
[0074] Example 6
[0075] The difference between Example 6 and Example 4 is only that step (2) is different, which is as follows:
[0076] Using the hydrothermal synthesis method, 1.0 g of LCTN electrode powder was added to 50 mL of 0.02 mol·L -1 After crystallization at 150°C for 4 hours in an aqueous solution of ferric nitrate nonahydrate, the obtained product was centrifuged, washed with water, dried, and then sintered at 800°C in air for 2 hours to obtain LCTN hydrothermally modified with iron oxide, which was recorded as LCTN-Fe.
[0077] Comparative Example 1
[0078] The difference between Comparative Example 1 and Example 4 is only that step (2) is different, which is as follows:
[0079] Using the hydrothermal synthesis method, 1.0 g of LCTN electrode powder was added to 50 mL of 0.02 mol·L -1After crystallization at 150 °C for 4 hours in a hexahydrated cobalt nitrate aqueous solution, the mixture was centrifuged, washed with water, and dried, and then sintered at 800 °C in air for 2 hours to obtain a cobalt oxide hydrothermally modified LCTN, which was recorded as LCTN-Co.
[0080] Comparative Example 2
[0081] The difference between Comparative Example 2 and Example 1 is that, in the preparation process of the solid oxide single cell, the LCTN electrode powder synthesized in step (1) of Example 1 is used as the fuel electrode, LSGM is used as the solid electrolyte support, and LSCF-GDC is used as the air electrode to assemble the solid oxide single cell. In order to investigate the effect of surface hydrothermal modification of metal oxide nanoparticles on the electrocatalytic activity of perovskite materials, the LCTN powder synthesized by the solvothermal method is not subjected to hydrothermal modification. Before the electrochemical performance test of the solid oxide single cell, the LCTN fuel electrode is reduced with hydrogen at 750°C for 2 hours to precipitate metal nickel particles, thereby forming a perovskite-type fuel electrode with a "metal nanoparticle-perovskite oxide" heterostructure.
[0082] Comparative Example 3
[0083] The difference between Comparative Example 3 and Example 1 is that, in the preparation process of the solid oxide cell, the solid oxide cell is assembled using the LCTN-Ce005M-2h prepared in step (2) of Example 1 as the fuel electrode, LSGM as the solid electrolyte support, and LSCF-GDC as the air electrode. In order to investigate the effect of in-situ precipitated metal nanoparticles on the electrocatalytic activity of the perovskite material, the LCTN-Ce005M-2h powder modified with cerium oxide surface is not subjected to reduction treatment. That is, before the solid oxide cell is subjected to electrochemical performance testing, hydrogen is not introduced for reduction. It can be considered that the "metal nanoparticle-perovskite oxide" heterostructure is not formed on the surface of the perovskite fuel electrode at the initial stage of the reaction.
[0084] Comparative Example 4
[0085] The difference between Comparative Example 4 and Example 1 is that, in the preparation process of the solid oxide cell, the LCTN electrode powder synthesized in step (1) of Example 1 is used as the fuel electrode, LSGM is used as the solid electrolyte support, and LSCF-GDC is used as the air electrode to assemble the solid oxide cell. In order to investigate the effects of surface hydrothermal modification of metal oxide nanoparticles and in-situ precipitation of metal nanoparticles on the electrocatalytic activity of the perovskite material, neither the LCTN powder is hydrothermally modified nor the LCTN fuel electrode of the solid oxide cell is reduced. It can be considered that the surface of the perovskite fuel electrode at the initial stage of the electrochemical performance test has neither the "metal nanoparticle-perovskite oxide" heterogeneous structure nor the hydrothermally modified metal oxide nanoparticles.
[0086] Material Characterization and Performance Testing
[0087] 1. Material Characterization
[0088] Figure 1 This is the X-ray powder diffraction pattern of the perovskite fuel electrode prepared in Example 1-3 of the present invention, wherein the abscissa 2theta represents the diffraction angle 2θ, and the ordinate Intensity represents the intensity of the diffraction peak. Figure 1 It was shown that LCTN was successfully synthesized by a solvothermal method, and different contents of cerium oxide were successfully modified on the perovskite material by a hydrothermal method.
[0089] Figure 2 The scanning electron microscope image and EDS spectrum image of the perovskite fuel electrode prepared in Examples 1-3 of the present invention, wherein: the abscissa Energy represents the energy of the X-ray, and the ordinate Intensity represents the intensity of the X-ray. Figure 2 It can be seen that after the perovskite fuel electrode powder was treated with pure hydrogen at 750°C for 2 hours, in-situ precipitated metal nickel particles can be observed on the surface of the perovskite grains, with a size range of 30-60nm, corresponding to Figure 2 (a) midpoint (1), Figure 2 (b) midpoint (2) and Figure 2 (c) midpoint (3), namely Point (1), Point (2) and Point (3). There are many tiny nanoparticles near the precipitated nickel particles and on the outer surface of the LCTN grains, which are hydrothermally modified cerium oxide nanoparticles with a particle size of less than 10nm. Among them: the cerium oxide content of the surface modified LCTN-Ce005M-2h prepared in Example 1 is 0.81%, see Figure 2 (a) Extend the hydrothermal time to 4 hours and maintain the concentration of cerium nitrate aqueous solution at 0.005 mol·L -1 The cerium oxide content of the surface modified LCTN-Ce005M-4h increased to 1.46%, see Figure 2 (b) The hydrothermal time was extended to 4 h and the concentration of the cerium nitrate aqueous solution was increased to 0.02 mol·L -1 The cerium oxide content of the surface modified LCTN-Ce02M-4h was further increased to 2.05%, see Figure 2 (c) This shows that the content of metal oxides hydrothermally modified on the outer surface of perovskite can be regulated by changing the hydrothermal treatment time and the concentration of the metal nitrate aqueous solution.
[0090] Figure 3 X-ray powder diffraction patterns of the perovskite fuel electrodes prepared in Examples 4-6 and Comparative Example 1 of the present invention, wherein the abscissa 2theta represents the diffraction angle 2θ, and the ordinate Intensity represents the intensity of the diffraction peak. Figure 3 It was shown that LCTN was successfully synthesized by a solid phase method, and cerium oxide (CeO2), zinc oxide (ZnO), iron oxide (Fe2O3) and cobalt oxide (Co3O4) were successfully modified on the perovskite material by a hydrothermal method.
[0091] Figure 4 This is a scanning electron microscope image of the perovskite fuel electrode prepared in Example 4 of the present invention. After being treated with pure hydrogen at 800°C for 2 hours, a perovskite fuel electrode material with in-situ precipitation of metallic nickel nanoparticles modified on the surface of cerium oxide can be obtained. Figure 4 It can be seen that larger in-situ precipitated nickel particles (60-120 nm) can be observed on the surface of the LCTN-Ce electrode after reduction treatment, and there are many smaller hydrothermally modified cobalt oxide nanoparticles (<10 nm) near the nickel particles and on the surface of the perovskite grains, see Figure 4 Enlarged image in upper right corner.
[0092] 2. Performance Testing
[0093] The electrochemical performance test process of the solid oxide single cell is as follows: the solid oxide single cells prepared in Examples 1-3 are heated to 750°C, and the fuel electrode is fed with 50 mL·min -1 Nitrogen and air were introduced at 50 mL / min. -1 Air. Change the fuel electrode atmosphere to 50 mL min -1 Hydrogen reduction was performed for 2 h to precipitate metallic nickel particles, and then the flow rate was changed to 25 mL min -1 Hydrogen and 25 mL min -1 The electrochemical impedance spectroscopy of the prepared battery was tested at 750°C in this atmosphere. The results are as follows Figure 5 As shown (the horizontal axis Z' represents the real impedance, Frequency represents the frequency, and the vertical axis -Z" represents the imaginary impedance). Figure 5 It can be seen that the solid oxide single cell with LCTN-Ce005M-4h as the fuel electrode has the smallest polarization impedance, which is about 0.29Ω·cm 2 , indicating that the hydrothermal modification of cerium oxide with a content of 1.46% on the LCTN surface showed the best electrocatalytic activity.
[0094] Figure 6 The RSOC performance diagram of the solid oxide single cell prepared in Example 1, wherein the horizontal axis Currentdensity represents the current density, the left vertical axis Voltage represents the voltage, and the right vertical axis Powerdensity represents the energy density. Figure 6It can be seen that the solid oxide single cell can use hydrogen to generate electricity (SOFC mode) and electrolyze carbon dioxide (SOEC mode) under the conditions of 750°C and 50% H2 / 50% CO2; and the maximum output power density in SOFC mode can reach 345mW·cm -2 , the electrolysis current density of CO2 electrolysis at 1.3V is -0.4A·cm -2 .
[0095] The electrochemical performance test process of the solid oxide symmetrical battery is as follows: the solid oxide symmetrical batteries prepared in Examples 4-6 and Comparative Example 1 are respectively heated at 50 mL·min -1 Heat to 800°C in nitrogen, and replace nitrogen with 50 mL / min -1 Hydrogen reduction was performed for 2 h to precipitate nickel particles, and then the reaction mixture was changed to 25 mL min -1 Hydrogen and 25 mL min -1 The reversible electrochemical performance of the prepared symmetrical battery was tested at 800°C in this atmosphere. Figure 7 As shown (the horizontal axis Z' represents the real impedance, Frequency represents the frequency, and the vertical axis -Z" represents the imaginary impedance). In addition, the electrochemical performance of the solid oxide symmetric cell (LCTN) assembled with the LCTN fuel electrode without any surface modification was tested to analyze the effect of the surface hydrothermal modified metal oxide on the electrocatalytic activity of the fuel electrode. Compared with the solid oxide symmetric cell with LCTN as the electrode, the solid oxide symmetric cell with LCTN-Fe as the electrode prepared in Example 6 has the smallest polarization impedance, which is about 7.1Ω·cm 2 ; The polarization impedance of the solid oxide symmetrical cell with LCTN-Co as the electrode prepared in Comparative Example 1 is even larger, indicating that after the hydrothermal modification of iron oxide on the surface of LCTN, it exhibits the best electrocatalytic activity, but the hydrothermal modification of cobalt oxide is not conducive to improving the electrocatalytic activity of the LCTN fuel electrode.
[0096] The electrochemical impedance spectrum of the solid oxide single cell prepared in Comparative Example 2 at 750°C and 50% H2 / 50% CO2 is as follows: Figure 8 As shown (the horizontal axis Z' represents the real impedance, Frequency represents the frequency, and the vertical axis -Z" represents the imaginary impedance). Figure 8 It can be seen that the solid oxide single cell with LCTN as the fuel electrode without any surface hydrothermal modification and only with the "metal nanoparticle-perovskite oxide" heterostructure has a polarization impedance of about 1.44Ω·cm 2 The polarization impedance of the solid oxide single cell assembled from the LCTN fuel electrode with different cerium oxide contents modified by surface hydrothermal in Example 1 was 0.29-1.22Ω·cm under the same conditions.2 , which are all smaller than the polarization impedance of the single cell prepared in Comparative Example 2, indicating that the electrocatalytic activity of the perovskite fuel electrode with only the "metal nanoparticles-perovskite oxide" heterostructure is inferior to the electrocatalytic activity of the perovskite fuel electrode with the "metal nanoparticles-perovskite oxide" heterostructure whose surface is hydrothermally modified with metal oxide nanoparticles.
[0097] The electrochemical impedance spectrum of the solid oxide single cell prepared in Comparative Example 3 at 750°C and 50% H2 / 50% CO2 is as follows: Fig. 9 As shown (the horizontal axis Z' represents the real impedance, Frequency represents the frequency, and the vertical axis -Z" represents the imaginary impedance). Fig. 9 It can be seen that the LCTN-Ce005M-2h with a surface hydrothermal modification of cerium oxide content of 0.81% is used as a fuel electrode without the "metal nanoparticle-perovskite oxide" heterostructure. The polarization impedance of the assembled solid oxide single cell is about 2.09Ωcm 2 , which is greater than the polarization impedance (about 0.99Ω·cm) of the solid oxide single cell assembled with the perovskite fuel electrode having a surface hydrothermally modified cerium oxide content of 0.81% and a "metal nanoparticle-perovskite oxide" heterostructure in Example 1 under the same conditions. 2 ), indicating that the electrocatalytic activity of the perovskite fuel electrode with only surface hydrothermal modification and no "metal nanoparticle-perovskite oxide" heterostructure is not as good as the electrocatalytic activity of the perovskite fuel electrode with "metal nanoparticle-perovskite oxide" heterostructure with surface hydrothermal modification of metal oxide nanoparticles.
[0098] The electrochemical impedance spectrum of the solid oxide cell prepared in Comparative Example 4 at 750°C and 50% H2 / 50% CO2 is as follows: Fig.10 As shown (the horizontal axis Z' represents the real impedance, Frequency represents the frequency, and the vertical axis -Z" represents the imaginary impedance). Fig.10 It can be seen that there is neither a "metal nanoparticle-perovskite oxide" heterostructure nor a perovskite fuel electrode with surface hydrothermal modified metal oxide nanoparticles. The polarization impedance of the assembled solid oxide single cell is about 2.48Ω·cm 2 , which is greater than the solid oxide single cell polarization impedance (about 1.44Ω·cm) of the fuel electrode in Comparative Example 2, which only has a "metal nanoparticle-perovskite oxide" heterostructure. 2 ), and also greater than the single cell polarization impedance of the solid oxide with a cerium oxide content of 0.81% in Comparative Example 3 (about 2.09Ω·cm 2), which is greater than the solid oxide single cell polarization impedance (about 0.99Ω·cm) of the fuel electrode in Example 1, which has a surface hydrothermal modification of cerium oxide content of 0.81% and a "metal nanoparticle-perovskite oxide" heterostructure. 2 ). This indicates that surface hydrothermal modification of metal oxide nanoparticles and "metal nanoparticle-perovskite oxide" heterostructures can significantly improve the electrocatalytic activity of perovskite fuel electrodes.
[0099] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A perovskite fuel electrode, characterized in that: It comprises metal nanoparticles, perovskite oxide and metal oxide nanoparticles; the metal nanoparticles are in-situ precipitated on the surface of the perovskite oxide and form a heterostructure with the perovskite oxide; the metal oxide nanoparticles are modified on the outer surface of the perovskite oxide.
2. The perovskite fuel electrode according to claim 1, characterized in that: The metal nanoparticles are transition metals, and the transition metal is selected from at least one of nickel, iron, cobalt, and ruthenium; and / or the particle size of the metal nanoparticles is 30-120 nm.
3. The perovskite fuel electrode according to claim 1, characterized in that: The metal oxide nanoparticles include at least one of cerium oxide, nickel oxide, iron oxide, copper oxide, and zinc oxide; and / or the particle size of the metal oxide nanoparticles is less than 10 nm.
4. The perovskite fuel electrode according to claim 1, characterized in that: The molar ratio of the metal nanoparticles to the perovskite oxide is (0.04-0.08):
1.
5. The perovskite fuel electrode according to claim 1, characterized in that: The mass ratio of the metal oxide nanoparticles to the perovskite oxide is (0.5-2.5):
100.
6. A method for preparing a perovskite fuel electrode, characterized in that: The preparation method is used to prepare the perovskite fuel electrode according to any one of claims 1 to 5, comprising the following steps: (1) synthesizing ABO3 type perovskite oxide with A-site defect and B-site metal doping to obtain electrode powder; (2) adding the electrode powder to a metal nitrate aqueous solution to carry out a hydrothermal reaction, and after centrifugation, washing with water, and drying, calcining in an air atmosphere to obtain an electrode powder modified with metal oxide nanoparticles; (3) The electrode powder modified with the metal oxide nanoparticles is subjected to heat treatment in a reducing atmosphere to precipitate metal nanoparticles in situ on the surface of the electrode powder, thereby obtaining the perovskite fuel electrode.
7. The method for preparing a perovskite fuel electrode according to claim 6, characterized in that: In step (2), the metal nitrate aqueous solution is selected from at least one of cerium nitrate, nickel nitrate, iron nitrate, copper nitrate and zinc nitrate; and / or the concentration of the metal nitrate aqueous solution is 0.05-0.5 mol / L; and / or the molar ratio of the electrode powder to the metal nitrate is (0.5-8.5):
1.
8. The method for preparing a perovskite fuel electrode according to claim 6, characterized in that: In step (2), the temperature of the hydrothermal reaction is 120-180° C.; and / or, the time of the hydrothermal reaction is 1-10 hours; and / or, the temperature of the calcination is 600-800° C.; and / or, the time of the calcination is 2-4 hours.
9. The method for preparing a perovskite fuel electrode according to claim 6, characterized in that: In step (3), the heat treatment temperature is 750-800° C.; and / or the heat treatment time is 1-3 hours.
10. A reversible solid oxide battery, characterized in that: It comprises a perovskite fuel electrode as described in any one of claims 1 to 5; or it comprises a perovskite fuel electrode prepared by the preparation method as described in any one of claims 6 to 9.
Citation Information
Patent Citations
Perovskite catalyst and preparation method thereof
CN113332992A
In-situ precipitation method self-assembled core-shell structure nanoparticle modified perovskite oxide electrode material, preparation method and application thereof
CN113948714A
Nano-catalyst-loaded perovskite composite anode and preparation method and application thereof
CN114243029A
Perovskite type solid oxide battery electrode catalyst, preparation method and application
CN115548356A
Surface modification method of perovskite oxide cathode and application of perovskite oxide cathode in solid oxide electrolytic tank
CN118291993A